2017
DOI: 10.17219/dmp/65519
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dental anxiety on the dental status of adult patients in the Lodz region

Abstract: StreszczenieWprowadzenie. Według danych z piśmiennictwa lęk stomatologiczny, który w różnych populacjach dotyczy od 16 do 24% dorosłych, może mieć wpływ na zachowania prozdrowotne związane z leczeniem dentystycznym oraz na stan uzębienia.Cel pracy. Ocena wpływu poziomu lęku przed leczeniem stomatologicznym na stan uzębienia dorosłych pacjentów z regionu łódzkiego.Materiał i metody. Do badania zakwalifikowano 140 losowo wybranych dorosłych zgłaszających się do Centralnego Szpitala Klinicznego UM w Łodzi od styc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
3
2
0
Order By: Relevance
“…This result is almost similar to the one obtained in the study of the Łódz region population, in which, however, another non-validated method was used. 33 It is also similar to the results achieved in other studies with the original version of the DAS scale and its adaptations, which is another premise of its validity.…”
Section: Discussionsupporting
confidence: 88%
“…This result is almost similar to the one obtained in the study of the Łódz region population, in which, however, another non-validated method was used. 33 It is also similar to the results achieved in other studies with the original version of the DAS scale and its adaptations, which is another premise of its validity.…”
Section: Discussionsupporting
confidence: 88%
“…From the studies on the cause of dentophobia, we obtained similar results to those in a study by K. Sopińska [6]. In our study, 68.4% of respondents indicated that their fear began in childhood due to negative experiences related to dental treatment; in [6], a similar cause of dentophobia was indicated by 85% of respondents [6].…”
Section: Discussionsupporting
confidence: 86%
“…In our analysis as well as in the study by Krufczyk, the respondents recognized that the personality traits of a dentist are important and can help reduce the stress caused by a visit [ 11 ]. From the studies on the cause of dentophobia, we obtained similar results to those in a study by K. Sopińska [ 6 ]. In our study, 68.4% of respondents indicated that their fear began in childhood due to negative experiences related to dental treatment; in [ 6 ], a similar cause of dentophobia was indicated by 85% of respondents [ 6 ].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations